Vertical Differentiation and Collusion: Cannibalization or Proliferation? - Jean J. Gabszewicz; Marco A. Marini; Ornella Tarola (Fondazione Eni Enrico Mattei (FEEM), 2016)
In this paper, we tackle the dilemma of pruning versus proliferation in a vertically differentiated oligopoly under the assumption that some firms collude and control both the range of variants for sale and their corresponding prices, likewise a multiproduct firm. We analyse whether pruning emerges and, if so, a fighting brand is marketed. We find that it is always more profitable for colluding firms to adopt a pricing strategy such that some variants are withdrawn from the market. Under pruning, these firms commercialize a fighting brand only when facing competitors in a low-end market. The same findings do not hold when firms are horizontally differentiated along a circle.
Keywords: D42; D43; L1; L12; L13; L41; 330; Vertically Differentiated Markets; Cannibalization; Market Pruning; Price Collusion